Double-crash on L4 Nerve Root at Different Segments - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2016)
Although lumbar disc herniation is one of the most common pathologies in neurosurgery, each patient has different challenges. With multiple level disc herniation, decision making process gets more complicated. Here we report a unique case with multiple level herniation that both compress the same nerve root. 62 Year-old woman admitted with left leg pain and her neurological examination showed weakness on quadriceps femoris and reduced patellar reflex. Imaging studies show L3-4 paramedian and L4-5 far-lateral disc herniation, both of which compress left L4 root causing a double-crash. She was operated with a median incision conformed for L3-4 standard discectomy and extended slightly caudally. This approach permitted L3-4 hemilaminectomy and L4-5 extra foraminal approaches. Patients are rarely symptomatic from multiple level disc herniation and multiple level discectomy should be exceptionally rare. A thorough neurologic examination is vital for multiple level disc herniation and usually point an individual level that causes symptoms. This patient is a unique example that needs multiple level discectomy although her neurologic examination shows compression on a single nerve root. A midline incision slightly extended caudally is sufficient to expose both levels in a patient with double-crash.
Keywords: Double-crash; single; nerve root; multiple level lumbar disc herniation; far lateral; LUMBAR DISC HERNIATIONS